Avaliação microbiológica de hortaliças em relação ao tempo, temperatura e produtos saneantes - Medeiros, Laissa Benites (2014)
The aim of this study was to evaluate the microbiota of vegetables under different conditions of time and temperature. We evaluated samples of lettuce, tomatoes, carrots and beets randomly collected from supermarkets in Santa Maria (RS). The samples of lettuce and tomatoes were divided in 3 treatments: Lettuce and tomato with skin in natura without sanitizing; cleaned with powder sodium hypochlorite, and sanitary water. We also analyzed peeled samples of carrots and beets washed with potable water only (not sanitize). After the washing and sanitizing procedure was performed, the samples were incubated in 3 different temperatures (10 ºC, 20 ºC and 30 º C) for 4 hours. Samples were collected at time 0 (To) indicating the initial contamination level of each sample and after 1, 2, 3 and 4 hours of exposure at the temperatures of 10 °C, 20 °C and 30 °C (T1, T2, T3 and T4). In each sample we evaluated the total count of psychrophilic and mesophilic aerobic, presence of Staphylococcus positive coagulase, Salmonella ssp. and the determination of the Most Probable Number of Total and thermotolerant coliforms. The results were expressed as log Log UFC/g. The highest averages in the total count of mesophilic aerobic microorganisms in samples of sanitized lettuce and tomatoes were found in the samples washed with water, apart of the temperature in which they were submitted. In the total count of mesophilic aerobic microorganisms in tomato samples the lowest averages were found at 10 ºC. In the samples of beet, we concluded that in the count of mesophilic aerobic, the increase was directly proportional to the exposure time at 30 ºC. In the carrot samples we found the lowest averages at 10 ºC. In none of the samples were found Salmonella ssp, Staphylococcus positive coagulase and thermotolerant coliforms. We conclude that apart of temperature, time and method of sanitizing all samples were within the acceptable limits required by law, and we highlight that these foods can be exposed to a higher temperature than the laws of Brazil bring, without endangering consumer health.